USING OF RANDOM DRIFT PARTICLE SWARM OPTIMIZATION (RDPSO) ALGORITHM ON ECONOMIC DISPATCH CONSIDERING WIND ELECTRICAL POWER FOR EMISSION REDUCTION - Mikhael Vidi Santoso; Rony Seto Wibowo; Adi Soeprijanto (Jurnal Teknik ITS, 2016)
Optimization technique is a treatment to increase the value of efficiency and effectiveness of an industrial system and for obtaining an objective optimal of system. Optimization technique, itself, is used in industrial sector a lot enough, particularly in the fields of energy industry, where other industries sector, such as manufacturing, transportation, and telecommunications, including the provision. As user optimization technique within period of quite long time, energy industry facing a wide range of issues, such as climate change, the use of tissues and reliability, the repeated construction of a system, and many more. Optimization technique helps companies in the field of energy through these issues with a better way and faster decisions. Economic dispatch (or ED) is one of the main problems towards energy companies. Economic dispatch (ED) is essential in control and power system. On this Final Project, the method offered is a method of modification of Particle Swarm Optimization, namely Random Drift Particle Swarm Optimization (RDPSO) Algorithm. RDPSO could produce the power 0.15% more efficient and 78% faster to reach the convergent point.